Spektralna Optyczna Koherentna Tomografia (SOCT) w diagnostyce chorób plamki – wyniki własne - Kałużny, Jakub; Szwagierek, Anna; Wojtkowski, Maciej; Kałużny, Bartłomiej; Kowalczyk, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
In this paper general information about spectral optical coherent tomography (SOCT) is presented. SOCT was used in diagnosis of choroidal neovascularization (16 eyes), central serous chorioretinopathy (4 eyes), macular hole (8 eyes), epiretinal membrane (3 eyes) and familial dominant drusen (2 eyes). In all cases SOCT examination revealed new data useful in detailed diagnosis. SOCT is a valuable complementary examination to fluorescein and indocianine green angiography in diagnosis of macula diseases.